Relationship between Atherogenic Index of Plasma with HbA1c Levels in Type 2 Diabetes Mellitus Patients - Ni Putu Sukma Sumantri Prabandari; Ida Ayu Putri Wirawati; Ni Nyoman Mahartini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Type 2 Diabetes Mellitus (T2DM) is a global health problem due to an increasing prevalence and incidence. HbA1c as a parameter for glycemic control is still above the desired target of 7%. Atherogenic Index of Plasma (AIP) is predicted to be an indicator of cardiovascular disease risk in T2DM. Dyslipidemia in T2DM patients showed a result of increased triglyceride and decreased HDL cholesterol levels. This study aimed to determine the relationship between HbA1c and AIP, triglycerides, and HDL cholesterol in T2DM patients. An analytical observational study using a cross-sectional method on 74 DMT2 patients who underwent HbA1c and lipid profile examinations in January-March 2020. Atherogenic index of plasma was calculated by the logarithmic equation (triglycerides/HDL cholesterol). Data were analyzed by SPSS 25.0. The relationship between HbA1c with AIP, triglycerides, and HDL cholesterol using the Pearson correlation test. Atherogenic index of plasma (0.25±0.25) and triglycerides (211.92±146.09 mg/dL) were found to be higher in the poor glycemic control group (HbA1c> 7%) than AIP (-0.04±0.20) and triglycerides (108.96±38.96 mg/dL) in the good glycemic control group (p < 0.05). HDL cholesterol (40.08±12.64 mg/dL) was found to be higher in the poor glycemic control group than HDL cholesterol (52.28±18.12 mg/dL) in the good glycemic control group (p < 0.05). There was a significant positive correlation between HbA1c and AIP (r=0.411, p=0.000), HbA1c with triglycerides (r=0.418, p=0.000), and a significant negative correlation between HbA1c and HDL cholesterol (r=-0.233, p=0.046). Insulin resistance can cause lipid metabolism disorders, inflammation, oxidative stress, and coagulation disorders. Maintaining glycemic control and lipid control plays an important role in preventing diabetes complications. There is a significant positive correlation between HbA1c and AIP, HbA1c and triglycerides, and a significant negative correlation between HbA1c and total cholesterol in T2DM patients.